Reflexões quanto à formação de professores para a disciplina projeto de vida: um olhar sobre a educação socioemocional - Alves, Maria Rosa Melo (2021)
Formative teaching processes in socioemotional education are essential to take basic education beyond cognitive conceptions level. In order to be effective and complete, education must take into account all aspects that develop an individual. This study aims at understanding the impact of continued socioemotional educational courses on teaching practice. This is a qualitative investigation based on semi-structured interviews with six elementary teachers from a public state school in Sergipe. The audio records were transcribed and discussed based on the content analysis of Bardin (1977). The categories and subcategories were built from the theoretical framework and semantic criteria that stood out in the participants' responses. With the related representations, four categories were created: teacher training, socioemotional education, teaching practice and working condition. The preliminary results showed that teacher training did not approach pedagogical didactic models that consider socioemotional education and, therefore, they had difficulty in preparing lesson plans that intentionally contemplate non-cognitive aspects rather than formative processes. In relation to the representations about being a Life Project teacher, with regard to socioemotional education, we noticed that the proposed themes for the discipline favor the affectivity between teachers and students and the change in the teaching imagination regarding the perception they had of the students. This fact enabled a narrowing of the student-teacher relationship. However, regarding to the working condition, the speech analysis showed the prevalence of negative nuances as to the availability of pedagogical support materials and the relationships between fellow professors from other subjects. It is hoped that the results will enable an analysis of the contribution of teacher training courses in socioemotional education in a perspective of reframing teacher praxis.